Advancing Forensic Flood Analysis Through Hydraulic Physical Models - Miguel Angel Sanchez-Quijano; Alfonso Gutierrez-Lopez; Fernanda Gonzalez Lagunas (Jurnal Teknik Hidraulik)
Urban density significantly increases the multi-hazard risks caused by extreme weather events. In Latin America and the Caribbean (LAC) countries, flood damages in urban areas are considerable and have shown a consistent annual increase. This challenge has prompted innovative educational responses to address the growing need for understanding and managing urban flood risks effectively. As part of postgraduate education efforts, the International Flood Initiative under the Intergovernmental Hydrological Programme of UNESCO for the LAC region (IFI-LAC IHP-UNESCO) aims to enhance understanding of vulnerability and flood risk estimation in urban settings. The initiative encourages the development of advanced hydro-informatic tools, watershed and river modeling techniques, and scale prototype construction to foster practical learning.